2012
DOI: 10.1007/s10653-012-9489-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk of respiratory and cardiovascular hospitalisation with exposure to bushfire particulates: new evidence from Darwin, Australia

Abstract: The risk of hospitalisation from bushfire exposure events in Darwin, Australia, is examined. Several local studies have found evidence for the effects of exposure to bushfire particulates on respiratory and cardiovascular hospital admissions. They have characterised the risk of admission from seasonal exposures to biomass air pollution. A new, unanalysed data set presented an additional chance to examine unique exposure effects, as there are no anthropogenic sources of particulates in the vicinity of the expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Other air pollutants from wildfires were less studied and their impact on cardiovascular illness remains unclear. Study findings varied geographically, with no report of a statistically significant cardiovascular impact of wildfire smoke in any study from Australia and Canada (seven out of 14) (Crabbe 2012; Hanigan et al , 2008; Henderson et al , 2011; Johnston et al , 2007; Martin et al , 2013; Moore et al , 2006; Morgan et al , 2010). Contrastingly, five out of six U.S. studies reported that exposure to wildfire smoke was associated with hospital admissions for cardiovascular diseases, such as cardiac arrests, or symptoms such as chest pain (Delfino et al , 2009; Lee et al , 2009; Rappold et al , 2012; Rappold et al , 2011).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Other air pollutants from wildfires were less studied and their impact on cardiovascular illness remains unclear. Study findings varied geographically, with no report of a statistically significant cardiovascular impact of wildfire smoke in any study from Australia and Canada (seven out of 14) (Crabbe 2012; Hanigan et al , 2008; Henderson et al , 2011; Johnston et al , 2007; Martin et al , 2013; Moore et al , 2006; Morgan et al , 2010). Contrastingly, five out of six U.S. studies reported that exposure to wildfire smoke was associated with hospital admissions for cardiovascular diseases, such as cardiac arrests, or symptoms such as chest pain (Delfino et al , 2009; Lee et al , 2009; Rappold et al , 2012; Rappold et al , 2011).…”
Section: Resultsmentioning
confidence: 92%
“…A U.S. study found that a 100µg/m 3 increase in wildfire smoke-related PM 2.5 was associated with a significant 42% (95%CI: 5%–93%) increase in emergency room visits for congestive heart failure (CHF) (Rappold et al , 2012). However, there were too few studies on specific cardiovascular endpoints, such as ischemic heart disease ( e.g ., Azevedo et al , 2011; Crabbe 2012; Moore et al , 2006) to establish consistency of associations.…”
Section: Resultsmentioning
confidence: 99%
“…Using the incidence of daily counts of hospital admissions for respiratory and cardiovascular diagnoses Crabbe et al [64] calculated the risk of hospitalization from wildfire exposure with respect to PM 10 , in Darwin, Australia. The results suggest that respiratory admissions were associated with exposure to PM 10 with a lag of 1 day when adjusted for flu and other confounders (RR = 1.025, 95 % CI: 1.000–1.051, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…PM is the predominant air pollutant seen in wildfire smoke, which is caused particularly by the burning of vegetation and wood. The health effects associated with particulate air pollution are well documented, and they are mostly related to the respiratory and cardiovascular functions (Analitis et al 2012;Anderson et al 2012;Betha et al 2014;Crabbe 2012;Delfino et al 2009;Johnston et al 2002;Pavagadhi et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research of wildfire effects was mainly focused on adult mortality and morbidity endpoints (Analitis et al 2012;Caamano-Isorna et al 2011;Crabbe 2012;Delfino et al 2009;Elliott et al 2013;Emmanuel 2000;Hanigan et al 2008;Johnston et al 2007;Vora et al 2011). However, to date, there is still limited research on the impact of wildfire smoke on vulnerable population groups, such as children (Jalaludin et al 2000;Künzli et al 2006;Mirabelli et al 2009).…”
Section: Introductionmentioning
confidence: 99%